Presenilin-1 influences processing of the acetylcholinesterase membrane anchor PRiMA - García-Ayllón, María-Salud; Campanari, María-Letizia; Montenegro, María-Fernanda; Cuchillo-Ibáñez, Inmaculada; Belbin, Olivia; Lleó, Alberto; Tsim, Karl; Vidal, Cecilio J.; Sáez-Valero, Javier (Neurobiology of aging, 2014)
Presenilin-1 (PS1) is the catalytic component of the γ-secretase complex. In this study, we explore if PS1 participates in the processing of the cholinergic acetylcholinesterase (AChE). The major AChE variant expressed in the brain is a tetramer (G4) bound to a proline-rich membrane anchor (PRiMA). Overexpression of the transmembrane PRiMA protein in Chinese hamster ovary cells expressing AChE and treated with the γ-secretase inhibitor N-[N-(3,5-difluorophenacetyl)-l-alanyl]-S-phenylglycine t-butyl ester have enabled us to study whether, through its γ-secretase activity, PS1 participates in the processing of PRiMA-linked AChE. γ-Secretase inhibition led to a notable increase in the level of PRiMA-linked AChE, suggesting that γ-secretase is involved in the cleavage of PRiMA. We demonstrate that cleavage of PRiMA by γ-secretase results in a C-terminal PRiMA fragment. Immunofluorescence labeling allowed us to identify this PRiMA fragment in the nucleus. Moreover, we have determined changes in the proportion of the raft-residing AChE-PRiMA in a PS1 conditional knockout mouse. Our results are of interest as both enzymes have therapeutic relevance for Alzheimer's disease.